Kepemimpinan Transformasional Kepala Sekolah Dalam Peningkatan Mutu Pendidikan di Sekolah SEKBIN IV Kecamatan Paguyangan - Muhammad Jafar; Nur Khoiri; Harto Nuroso (Jurnal Inovasi Pembelajaran di Sekolah, 2026)
This study aims to analyze the influence of the principal's transformational leadership on improving the quality of education in elementary schools in Sekbin IV, Paguyangan District, Brebes Regency. This study uses a qualitative approach with a multiple case study method involving three elementary schools as research subjects. Data were collected through observation, in-depth interviews with principals, teachers, and administrative staff, as well as related documentation. Data analysis was carried out inductively to identify patterns and themes related to the implementation of transformational leadership and its impact on the quality of education. The results of the study indicate that transformational leadership implemented by the principal in increasing teacher motivation, developing professional competence, and creating a collaborative and innovative learning environment. Effective leadership can help schools achieve improved student learning outcomes. The implementation of transformational leadership varies in each school, depending on the context and characteristics of each school. In conclusion, the principal's transformational leadership is a key factor in achieving improved quality of education in elementary schools. This study provides implications for the development of leadership training programs for principals to support continuous improvement in the quality of education.